Legal Regulations on Forced Migration and Voluntary Migration - Akgunduz, A. (The Journal of Rotterdam Islamic and Social Sciences, 2020)
This article begins by clarifying central Muslims concepts in the migrant debate: deportation, exile, voluntary migration (hijrah ) and forced migration (tahjîr ). It then looks at the issue of migrations and migrants prior to the Tanzimat (Reforms) period. This incorporates two subperiods: from the beginning of the Ottoman State to the 17th century, and from 1840 until the founding of the Republic of Turkey.. It then looks at developments and important legislation passed in the post-Tanzimat period, distinguishing three different developments in that larger period: restrictions on immigration the legal issue of Ottoman citizenship, and legal arrangements for immigrants after Tanzimat . The author’s emphasis throughout is on the Ottoman State’s welcoming attitude to immigrants, providing a contrast with standard Western practice.